Species composition and abundance of solpugids (Arachnida: Solifugae) in ecotopes of the transitional coastal desert of Chile - Daniel Eugenio Valdivia; Jaime Pizarro-Araya; Raúl Briones; Andrés A. Ojanguren-Affilastro; Jorge Cepeda-Pizarro (Revista Mexicana de Biodiversidad)
Using pitfall traps, the species composition and abundance of solpugids were studied in several ecotopes of Chile’s transitional coastal desert. The study was conducted in the area around Punta de Choros (29º15’S, 71º26’W) and in Los Choros Archipelago (29º32’S, 67º61’W), in 2005 and 2006. Five species were recorded: Procleobis sp.; Sedna pirata Muma, 1971 (Ammotrechidae); Mummucia sp.; Mummucia variegata (Gervais, 1849) (Mummuciidae); and Ammotrechelis goetschi Roewer, 1934 (Daesiidae). Solpugid abundance was higher on the continent (65%) than on the islands (35%). The ANOSIM used to evaluate any difference in species richness between ecotopes revealed no significant differences (R= 0.097, p= 0.13). The similarity dendrogram obtained from the Bray-Curtis matrix indicates that there are 3 groups of ecotopes: steppe, dune, and a miscellaneous group. From the data it is inferred that the diversity and abundance of solpugids in the ecotopes studied may be related to plant structure and to the pedological conditions of the habitat.